COMPARATIVE LITERATURE OF INDONESIAN FOLKLORE BAWANG MERAH AND BAWANG PUTIH AND RUSSIAN FAIRY TALE VASILISA THE BEAUTIFUL - Dwi Novitasari; Mansur (Universitas PGRI Ronggolawe Tuban, 2024)
Folklore has several similarities and differences, especially in the folklore of Bawang Merah and Bawang Putih and the fairy tale of Vasilisa The Beautiful, even though the two stories come from different countries. In finding the similarities and differences between the two folktales, the researcher uses a structural and comparative literary approach. This study aims to describe the similarities and differences between the two folktales. The method used in this research is a descriptive method. Data were analyzed using a qualitative approach with more emphasis on content analysis techniques. The approach used to analyze the two folktales is a structural approach and a comparative study. The results of the study show that the folklore of Bawang Merah and Bawang Putih and Vasilisa The Beautiful has several storylines, but has a similar conflict through the role of the stepmother which is represented through an evil character.